The Power of Lakshmi: Monetary Incentives for Raising a Girl - Nabaneeta Biswas; Christopher Cornwell; Laura V. Zimmermann (Global Labor Organization (GLO), 2021)
Worldwide, 1.6 million girls are "missing" at birth every year. One policy tool to improve the sex ratio is a conditional cash transfer that pays parents to invest in daughters, but existing evidence on their effectiveness is sparse. Using a difference-in-differences framework, we evaluate the Dhanlakshmi scheme, an Indian CCT program that strongly encouraged girl births without restricting fertility. Dhanlakshmi improved the sex ratio at birth, with only a small fertility increase. The girl-birth effect was concentrated among the first two parities and partially persisted after the program was discontinued. Post-birth outcomes like immunization and education also improved.
Keywords: D13; H53; I15; I18; J16; 330; conditional cash transfer; son preference; sex ratio; gender bias; India